2022
DOI: 10.1002/widm.1449
|View full text |Cite
|
Sign up to set email alerts
|

Methods and tools for causal discovery and causal inference

Abstract: Causality is a complex concept, which roots its developments across several fields, such as statistics, economics, epidemiology, computer science, and philosophy. In recent years, the study of causal relationships has become a crucial part of the Artificial Intelligence community, as causality can be a key tool for overcoming some limitations of correlation‐based Machine Learning systems. Causality research can generally be divided into two main branches, that is, causal discovery and causal inference. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…The retrospective design of this study remains a limitation, and the results reported may be due to observational biases and should not be assigned a causal interpretation. In particular, quantifying causal treatment effects from such observational data is an active area of research and such analysis is beyond the scope of this study 38,39 . The data gathering process is observational and whilst FCAL is collected routinely at all clinical interactions, subjects with more complicated disease are still likely to have more measurements available.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective design of this study remains a limitation, and the results reported may be due to observational biases and should not be assigned a causal interpretation. In particular, quantifying causal treatment effects from such observational data is an active area of research and such analysis is beyond the scope of this study 38,39 . The data gathering process is observational and whilst FCAL is collected routinely at all clinical interactions, subjects with more complicated disease are still likely to have more measurements available.…”
Section: Discussionmentioning
confidence: 99%
“…Causation describes the relationship between one factor and another in a system [26]. The former factor is the cause of the latter factor, and the latter factor is the result of the former factor.…”
Section: Causal Inference (Ci)mentioning
confidence: 99%
“…Further, we assume a feature matrix vector that contains all confounders , namely the variables that are causally influencing both the treatment and the outcome. Note that all confounders are observed, otherwise special causal effect learning methods need to be deployed [ 43 , 48 ]. Formally, the causal relations are represented graphically with Directed Acyclic Graphs (DAG), which means that the arrangement and orientation of the edges should not form any cycles.…”
Section: Proposed Approachmentioning
confidence: 99%